Hubungan Tingkat Kognitif Perawat tentang Caring dengan Aplikasi Praktek Caring di Ruang Rawat Inap RSU dr. H. Koesnadi Bondowoso (The Correlation between Nurses Cognitive Level on Caring with Caring Practice Application in the Inpatient Unit RSU dr. H. K - Bagus Setyo Prabowo; Anisah Ardiana; Dodi Wijaya (Pustaka Kesehatan, 2014)
Caring is one form of behavior exhibited by a nurse in performing nursing care services. Purpose of this study was to analyze correlation between nurses cognitive level on caring with caring practice application in the inpatient unit RSU dr. H. Koesnadi Bondowoso. Population in this study were 71 nurses RSU dr. H. Koesnadi Bondowoso with 41 nurses as sample. Nurse characteristics data analysis used univariate analysis, whereas for nurses cognitive levels and nurses caring practices application used the chi-square test with α significance level of 5%. Descriptive data analysis of nurses caring cognitive level showed that 26 nurses (56.5%) had good cognitive and 20 nurses (43.5%) had less cognitive. Applications caring practices showed 23 nurses (50.0%) behaved caring and 23 nurses (50.0%) behaved less caring. Results showed that p value = 0.037 with α significance level of 0.05, and thus Ho was rejected, which means there  was a correlation between nurses cognitive level on caring with caring practice application in the inpatient RSU. dr. H. Koesnadi Bondowoso. Odds ratio 4.4 which means the nurse who had good cognitive level on caring would 4,4 times behaved caring compared with nurses who had sufficient cognitive level of caring.   Keywords: cognitive level nurse, caring, caring practice application